Severe tumor lysis syndrome during the induction therapy for the treatment of blastic plasmacytoid dendritic cell neoplasm arising from myelodysplastic/myeloproliferative neoplasms. Issue 2 (20th December 2020) - Sagou, Ken; Ito, Makoto; Kawamura, Yuma; Ukai, Shun; Goto, Miyo; Fukushima, Nobuaki; Ozeki, Kazutaka; Fukuyama, Ryuichi; Kohno, Akio
Abstract: BPDCN shows clinically heterogeneous characteristics. And as other hematological malignancies, symptoms of BPDCN suggesting a high tumor burden, such as high white blood cell count or splenomegaly, should be carefully considered to prevent TLS. Abstract : BPDCN shows clinically heterogeneous characteristics. And as other hematological malignancies, symptoms of BPDCN suggesting a high tumor burden, such as high white blood cell count or splenomegaly, should be carefully considered to prevent TLS.